Quantificação de resíduos de amoxicilina e ampicilina por injeção direta de amostras de leite de bovino - Moura, Franciane (2011)
The development of new methods for analysis and quantification of drugs and their metabolites in biological fluids is of great interest in various areas of knowledge. The pre-treatment of complex matrices is a fundamental step for the quantification of compounds in trace levels. Methods of direct injection of samples by 2D liquid chromatography systems have led to higher precision and accuracy, and quantification limits ever smaller. The use of RAM columns allows the exclusion of proteins and other macromolecules present in biological matrix and extraction of lower molecular weight analytes through hydrophobic, ionic or affinity interactions. In this work, a number of different RAM columns were evaluated with different materials adsorbed or bound on the silica surface (BSA, methylcellulose and - lactoglobulin). As well as, columns with different modes and mechanism of the analytes retention (C8, C18, SAX, SCX) were used. Using the technique of column coupling and a mass spectrometer as detector, ampicillin, was quantified, in bovine milk samples having a RAM-BSA column, in the first dimension coupled to an ACQUITY UPLC BEH column, in the second dimension. MRM mode with three specific transitions, 350> 106, 350> 160 and 350> 192 m/z, were monitored. The first, more intense, was used for quantification while the other two were used for confirmation. The developed method is simple, with analysis time of 14 minutes without any pretreatment of samples, except for centrifugation.